Corporate strategy - Lynch, Richard L. (Harlow, England ; New York : FT/Prentice Hall, 2006)
Provides contemporary coverage of both the prescriptive and emergent schools of strategy from a European rather than American perspective. This fourth edition contains new material on public sector strategy and updated coverage of organisational structures.
Includes bibliographical references and indexes.
nmn, 11/08/15
Loan
Keywords: Business planning; Strategic planning; Corporate strategy